Televised redemption: Black religious media and racial empowerment - Rouse, Carolyn Moxley (New York University Press, 2016)
Redemptive media histories -- Black Christian redemption: contested possibilities -- Racial redemption: language in Muslim media -- Divine redemption: Hebrew Israelites and the saving of the world -- Religious media and Black self-formation -- Reimagined possibilities: prosperity and the journey to redemption -- Race, Islam, and longings for inclusion: Muslim media and twenty-first-century redemption -- Citizens as stewards: on the air, online, and in the community